Sea cucumber-derived compounds for treatment of dyslipidemia: A review - Ping Lin; Nuo Shen; Fan Yin; Shou-Dong Guo (Frontiers Media S.A., 2022)
Dyslipidemias are disorders of plasma levels of lipids, such as elevated levels of total cholesterol and triglyceride, that are associated with various human diseases including cardiovascular disease (CVD) and non-alcoholic fatty liver disease (NAFLD). Statins are the first-line drugs for treatment of dyslipidemia. However, a substantial proportion of patients cannot reach the recommended LDL-c level even with the highest tolerated doses of statins, and there is no available drug specifically for NAFLD therapy. Sea cucumbers are one of the widely distributed invertebrates, and are an important resource of food and medicine. Sea cucumbers have many valuable nutrients including saponins, fatty acids, phospholipids, cerebrosides, sulfated polysaccharides, as well as proteins and peptides. In recent years, these natural products derived from sea cucumbers have attracted attentions for treatment of CVD and NAFLD because of their lipid-lowering effect and low toxicity. However, the hypolipidemic mechanisms of action and the structure-activity relationship of these bioactive components have not been well-documented in literature. This review article summarizes the signaling pathways and the potential structure-activity relationship of sea cucumber-derived bioactive compounds including saponins, lipids, carbohydrates as well as peptides and proteins. This article will provide information useful for the development of sea cucumber-derived lipid-lowering compounds as well as for investigation of hypolipidemic compounds that are derived from other natural resources.